Comparative Study on the Surface Morphology and Structural Degradation of Bio-based Polylactic Acid and Conventional High-Density Polyethylene - Rosli, Nur Insyirah; Asman, Saliza (Enhanced Knowledge in Sciences and Technology, 2026)
This work studied the surface morphology and molecular structure of bio-based and conventional plastics, specifically polylactic acid (PLA) and commercial-grade high-density polyethylene (HDPE). The degradation process was conducted over a period of 45 days under controlled hydrolytic conditions and natural sunlight exposure. The FTIR result revealed the formation of a new hydroxyl (-OH) peak at 3396  in PLA after degradation, indicating ester bond cleavage and the formation of degradation products. HDPE showed a very minimal spectral change, revealing its resistance to both hydrolytic and photo-oxidative degradation remained stable. The surface morphology analysis proved that HDPE had a comparatively constant and intact structure, while PLA showed increased roughness and surface defects. Overall, the results show that PLA is more particularly susceptible to environmental degradation compared to HDPE, which provides insights on how conventional and bio-based polymers degrade differently.